2012
DOI: 10.1016/j.chembiol.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Proteasome as a Therapeutic Target in Plasmodium Using an Epoxyketone Inhibitor with Parasite-Specific Toxicity

Abstract: Summary The Plasmodium proteasome has been suggested to be a potential anti-malarial drug target, however toxicity of inhibitors has prevented validation of this enzyme in vivo. We report here a screen of a library of 670 analogs of the recently FDA approved inhibitor, carfilzomib, to identify compounds that selectively kill parasites. We identified one compound, PR3, that has significant parasite killing activity in vitro but dramatically reduced toxicity in host cells. We found that this parasite-specific to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 28 publications
(39 reference statements)
5
118
0
3
Order By: Relevance
“…Toxicity and regulatory issue may make it difficult to reposition a clinically used proteasome inhibitor. Earlier efforts to develop Plasmodium -specific proteasome inhibitors [114116] now benefit from a recent tour de force , in which a collaboration led by Dr. Matt Bogyo (Stanford University) applied cryo-electron microscopy and single particle analysis to solve the structure of the P. falciparum 20S proteasome to a resolution of 3.6 Å. Combined with substrate profiling, this provides valuable information regarding active site architecture that can be used to drive optimal inhibitor design [92].…”
Section: Can Resistance To Arts Be Overcome?mentioning
confidence: 99%
“…Toxicity and regulatory issue may make it difficult to reposition a clinically used proteasome inhibitor. Earlier efforts to develop Plasmodium -specific proteasome inhibitors [114116] now benefit from a recent tour de force , in which a collaboration led by Dr. Matt Bogyo (Stanford University) applied cryo-electron microscopy and single particle analysis to solve the structure of the P. falciparum 20S proteasome to a resolution of 3.6 Å. Combined with substrate profiling, this provides valuable information regarding active site architecture that can be used to drive optimal inhibitor design [92].…”
Section: Can Resistance To Arts Be Overcome?mentioning
confidence: 99%
“…In particular, the strongly electrophilic carbonyl and epoxide groups are highly susceptible to a double nucleophilic attack by the N‐terminal threonine of the 20S proteasome, leading to the irreversible formation of a morpholino ring . Consequently, these natural products have inspired the current development of anticancer, anti‐inflammatory, and antiparasitic drugs with a terminal epoxyketone warhead . One such example is the synthetic epoxomicin analogue, carfilzomib (Scheme ), which has been used as a treatment for relapsed and refractory multiple myeloma …”
Section: Methodsmentioning
confidence: 99%
“…[15] PathwayA postulates the introduction of as ingle methyl group at C2, followed by the reductionoft he carboxylica cid to an olefin that can then undergo epoxidation,w hereas pathway Bp roposes dimethylation at C2, followed by decarboxylation of the carboxylic acid and subsequente poxide installation. [15] To distinguish between these two possibilities, we fed [1,2-13 C]sodium acetate to cultures of JL11, the highest producing strain, and compared the www.chembiochem.org resulting 13 Ci ncorporation to that from unlabeled and [1-13 C]sodium acetate feeding (Scheme2 and Figure S9-10).A lthought he titerso fl abeled 3 and 4 were insufficientf or NMR analysis, LC-HRMS analysis of 3 and 4 from the extracts of cultures fed with [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]sodium acetate showed as ignificant increase in the ratio of the M+ +1p eak intensity to the M+ + peak intensity compared to that of cultures fed with unlabeled and [1-13 C]sodium acetate (FiguresS9a nd S10). Further HRMS/MS analyses and examination of the isotope distribution of fragments with and withoutt he epoxyketone group indicated that this increase is the result of as ingle 13 Ca tom from doubly labeled acetate being incorporated as the C2 carbon of 3 and 4 after decarboxylation (Scheme 2a nd Figure S9-10).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[326] Die Verwendung einer aktivitätsbasierten Sonde in P. -falciparum-Kulturen, die mit selektiven, bekannten Inhibitoren der humanen b1-, b2und b5-Untereinheiten vorbehandelt waren, lieferte wichtige Einblicke in das 20S-Proteasom. [326] Die Verwendung einer aktivitätsbasierten Sonde in P. -falciparum-Kulturen, die mit selektiven, bekannten Inhibitoren der humanen b1-, b2und b5-Untereinheiten vorbehandelt waren, lieferte wichtige Einblicke in das 20S-Proteasom.…”
Section: Angewandte Chemieunclassified